La prensa temprana en la era digital: contexto y recursos - Poupeney-Hart, Catherine (2017)
The main obstacle to the study of the early periodical press has been access to the materials, due in part to their volume, but even more to their minor status as a scriptural practice. More particularly in Hispanic America, this prevented several newspaper series from being preserved intact and what survived was not always kept in optimal conditions. Even if we will have to wait until relevant libraries or archives provide digitized version of their full collections, the operations that have already taken place offer unprecedented access to materials with potential implications still difficult to foresee. This article aims initially to provide a brief and practical survey of the present situation. It will then move on to examine, from this perspective, the third series of the Gazeta de Guatemala (1797-1807), the most important newspaper at the end of the 18th and beginning of the 19th centuries in Hispanic America